2015
DOI: 10.3390/molecules200712732
|View full text |Cite
|
Sign up to set email alerts
|

Metal- and Semimetal-Containing Inhibitors of Thioredoxin Reductase as Anticancer Agents

Abstract: Abstract:The mammalian thioredoxin reductases (TrxRs) are a family of selenium-containing pyridine nucleotide disulfide oxidoreductases playing a central role in cellular redox homeostasis and signaling pathways. Recently, these selenoproteins have emerged as promising therapeutic targets for anticancer drug development, often being overexpressed in tumor cells and contributing to drug resistance. Herein, we summarize the current knowledge on metal-and semimetal-containing molecules capable of hampering mammal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 97 publications
1
48
0
Order By: Relevance
“…Since the intracellular redox conditions seem to play a key role in the establishment of the chronic phase of HCV infection, we decided to evaluate whether the oxidative stress could reactivate HCV replication in chronically infected cells. For this reason, a chemical treatment with auranofin (Au), a well-known prooxidant drug [39] that induces ROS production in infected cells [40,41], was used. In our experimental model, treatment with Au (200 nM) for 48 hrs was able to induce an increment of intracellular ROS levels by twofold, either in uninfected (CTR) or in HCV-infected cells (Figure 5(a)).…”
Section: Auranofin-induced Oxidative Stress Leads To Increasedmentioning
confidence: 99%
“…Since the intracellular redox conditions seem to play a key role in the establishment of the chronic phase of HCV infection, we decided to evaluate whether the oxidative stress could reactivate HCV replication in chronically infected cells. For this reason, a chemical treatment with auranofin (Au), a well-known prooxidant drug [39] that induces ROS production in infected cells [40,41], was used. In our experimental model, treatment with Au (200 nM) for 48 hrs was able to induce an increment of intracellular ROS levels by twofold, either in uninfected (CTR) or in HCV-infected cells (Figure 5(a)).…”
Section: Auranofin-induced Oxidative Stress Leads To Increasedmentioning
confidence: 99%
“…There are increasing metal complexes, especially the gold and platinum complexes, which have been reported as TrxR inhibitors . In this section, we reviewed the gold‐containing inhibitors first, and then platinum‐containing complexes.…”
Section: Thioredoxin Reductase Inhibitorsmentioning
confidence: 99%
“…[240] The Cterminal sequence containing the seleno-cysteine (Sec) residue has been identified as reactive towards several compounds, and such interaction was shown to inhibit the activity of the protein. Although cisplatin and gold-based (Au(I) and Au(III)) complexes have been described to inhibit TrxR using in vitro assays, [248][249][250][251][252][253][254][255][256][257][258] The results suggested that arsenic trioxide binds to both sulfur and selenium in the C-terminal motif GlyCysSecGly of the protein, and although precise identification of the coordination sites was not possible, the N-terminal sequence was also found to participate in the reaction with As. [263] However, it is worth mentioning that in this report, no evidence for the selenium isotopic pattern on the peptide fragment bound to arsenic has been provided.…”
Section: Seleno-enzymesmentioning
confidence: 99%